In situ characterization of an old railway platform with DCP - Fortunato, E. (2009)
The elastic stiffness measured in situ is considered a good indicator of the performance of railway platforms. The deformation modulus obtained from the Plate Load Test (PLT) is commonly considered representative of that stiffness. Nevertheless, the PLT is a very expensive and time consuming test. Moreover, it is very difficult to perform when the purpose is to characterize ancient platforms of railway lines that must be maintained active during the renewal works. The Dynamic Cone Penetrometer (DCP) is a much cheaper and simpler test, traditionally used to control the compaction of soils and granular materials. The paper reports the experience of the combined use of PLT and DCP tests for characterizing the platform of the main railway line in Portugal (built in the XIXth century), which has recently been upgraded to high speed passenger trains and freight trains with higher maximum axle load. Correlations between the average resistance to penetration of the DCP and the deformation modulus from PLT are presented for coarse-grained and fine-grained soils. A criterion is proposed for the depth over which the DCP results should be averaged for correlation with the modulus from the PLT.